Kefileme of the Christians of Sarajevo From 1788 - Kreševljaković, Hamdija (Prilozi za orijentalnu filologiju, 2017)
Kefileme was a nacessary measure of the Turskih judical-administrative service for maintenance of peace and order in times of trouble. This prevention measure was taken upon Vezier's order that all suspicious inhabitants of a town, village or region should guarantee for one another. The Vezier would issue an order (bujuruldija) to his representative (muteselim) or, if he was absent, to the quadi, to take the keftleme. The muteselim or the quadi would take the record ( defter) of all the men obliged according to the keftleme, noting who was guaranteeing for whom. This measure sometimes helped the authorities to prevent riots and rebellions. Sometimes the kefileme was taken after crushed riots. The list made on this occasion was called the "keftleme defter". The kefileme usually included male inhabitants more than 19 years old. Sometimes it included all the inhabitants of a town or region and sometimes only those belonging to a profession, e.g. tradesmen, or to a single confession. People guaranteed for one another in groups of two, three, or more. In a kefileme from 1848 there are groups of 150, 160 and even 170 people. All the kefllemes known so far were taken among Moslems or among inhabitants of all confessions. I know of only one keftleme taken exclusively among Christians (Ortodox and Catholics). The keftleme was written by the muteselim in three copies: one for the Vezi er, one for the quadi so that he could put it in the "sidžil", and one for the muteselim. The "Keftleme defter" was always accompanied by a written oath listing all the guaranties. In the 18th e. the nahija (district) of Zenica was all the time under the kefileme. The "Keftleme defter" was renewed every eight or ten years. The date of the introduction of this measure is not known. Although we do not know of other similar examples this was probably not an exception. Those who could not fmd a guarantor were expelled from the territory where kefileme was taken. The documents that we know tell us that the kefileme in Bosnia started in the middle of the 16th e. and was used tilll848 when the revolution in Austria broke out. In 1788 a kef.tleme was taken - it means during the war between Austria and Turkey. This list comprises 625 people: 26 women and 599 men (25 of them were absent from Sarajevo). They inhabited 12 quarters (mahalas) and three inns. This list tells us of the part that Christians took in the economic life of Sarajevo. There were 330 craftsmen and tradesmen and 98 servants. The profession of 136 men is not mentioned which does not mean that they did not have one. This paper also comprises the proclamation originally written in Turkish and addressed by Austria to the population of Bosnia and Herzegovina warning it not to take part in resistance and threatening those who should try to rebel.